Protein aerogels as food-grade delivery systems - A comprehensive review - Leite, Ana Catarina Carvalho Oliveira (2025)
Aerogels have gained considerable attention in recent years due to their unique properties, drawing interest from both the scientific community and industry. Yet, their potential in food applications remains largely unexplored. Protein-derived aerogels exhibit remarkable bioactivity, biocompatibility and biodegradability, showing promise as food-grade delivery systems. While there are numerous reports on food-grade aerogels derived from animal proteins, the use of non-animal proteins (NAPs) remains underrepresented. Additionally, protein-based aerogels, especially those derived from NAPs, can address concerns related to resource-intensive protein sourcing, environmental impact, health-related issues, and ethical concerns. Hence, this review aims to comprehensively understand the advances in protein aerogels, covering synthesis methods, bioactive compound-loading techniques, performance characterization, and release mechanisms. It also explores the potential food applications of these protein aerogels, focusing on the employment of NAPs. By consolidating the existing information, this review offers insights into the future development of protein aerogels and their applications as functional food ingredients. Protein aerogels have the potential to serve as components in food packaging or edible delivery systems, encapsulating bioactive compounds, extending shelf-life, serving as fat substitutes, and even masking odors and flavors.